2018
DOI: 10.3390/su10082716
|View full text |Cite
|
Sign up to set email alerts
|

What Does the Sustainability-Risk Interaction Look Like? Exploring Nuanced Relationships in Emerging Economy Sustainability Initiatives

Abstract: Abstract:To be viable long-term, sustainability programs must be profitable. Unfortunately, current sustainability practices increase risk, increasing costs and threatening revenues. Higher costs and lower revenues negatively impact profitability and, thus, the viability of sustainability. To understand how sustainability-induced risks affect food production systems, sustainability-induced risks in food production systems are identified and classified. It is also explored how sustainability risks interact, mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Theoretical relationships and building (Theory): Several approaches to integrate sustainability and resilience have been introduced. In many cases, the traditional triple bottom line dimensions of sustainability have been broadened to other constructs that have been becoming increasingly important, such as risk and knowledge (Closs et al, 2011; Göçer et al, 2018, 2019). Nevertheless, more holistic approaches have been recommended given the complexity and urgency of sustainability (Fiksel, 2006).…”
Section: Sustainable and Resilient Supply Chainsmentioning
confidence: 99%
“…Theoretical relationships and building (Theory): Several approaches to integrate sustainability and resilience have been introduced. In many cases, the traditional triple bottom line dimensions of sustainability have been broadened to other constructs that have been becoming increasingly important, such as risk and knowledge (Closs et al, 2011; Göçer et al, 2018, 2019). Nevertheless, more holistic approaches have been recommended given the complexity and urgency of sustainability (Fiksel, 2006).…”
Section: Sustainable and Resilient Supply Chainsmentioning
confidence: 99%
“…Göçer et al. [ 27 ] argued that the risks are interrelated and these risks should be considered in a holistic way through a dynamic process.…”
Section: Theoretical Background and Related Literaturementioning
confidence: 99%
“…To begin to understand the sustainability-risk-cost sequence in emerging economies, we recruited participants from five different Turkish food supply chains for interviews and on-site observations [63]. Specifically, we conducted 41 semi-structured interviews at 32 companies with managers and consumers by using an interview protocol assembled through a systematic literature review.…”
Section: Initial Case Study-risk Dimensions Salient To Environmental mentioning
confidence: 99%
“…These interviews typically lasted about an hour and were transcribed for interpretive analysis by multiple researchers [64,65]. This initial study identified five major risk categories [63], and established the baseline for comparison as interviews were conducted in the automotive, apparel, and white goods industries.…”
Section: Initial Case Study-risk Dimensions Salient To Environmental mentioning
confidence: 99%